Large power microwave nonlinear effects on multifunction amplifier chip for Ka-band T/R module of phased array radar - Guo, Guo; Gu, Ling; Wu, Ruowu; Xu, Xiong; Zhou, Taifu; Niu, Xinjian; Liu, Yinghui; Wang, Hui; Wei, Yanyu; Guo, Changyong (AIP advances, 2017)
Nonlinear effects of large power millimeter wave on critical chips for the T/R module of phased array radar is experimental studied and analyzed in this paper. A multifunction amplifier chip is selected for our experiments. A solid continuous wave (CW) source and a large power pulsed magnetron are both employed to generate the Ka-band microwave. The input-output characteristics, the degradation and destroy threshold of the chips are obtained through a series of experimental tests. At last, the results are given by figures and analyzed theoretically.